Employee turnover in Indonesia’s Directorate General of Taxes, a case study of Jakarta’s tax offices between 2009 and 2015: critical application of Price and Mueller’s causal model of turnover - Meliani, Lenny Erna (2018)
The thesis is driven by the increasing number of the Directorate General of Taxes (DGT) employees who voluntarily left the organisation following the first phase of its organisational reforms that ended in 2008. Some changes were made to the reforms, including improving the employee compensation scheme, developing a more conducive working environment, setting up standard operating procedures to clarify job ambiguity, and implementing a job rotation system. The expectation following these changes was that employees would perform better and continue their employment in the DGT. During the second phase of reform between 2009 and 2014, 280 DGT employees decided to quit their jobs. The DGT claimed it had lost many tax specialists, tax auditors and managers, who play a crucial role in enabling the DGT to perform its function of collecting tax revenues This thesis seeks to understand the underlying causes of employee turnover in Indonesia’s DGT. It employs Price and Mueller’s model of employee turnover as the analytical framework to systematically examine the research problem. The research is based on two case studies in Jakarta’s regional tax offices, and it includes former and current DGT employees, as well as officials who are responsible in implementing the human resource regulations. Data for the research were collected through questionnaires and interviews. Price and Mueller’s comprehensive approach to the turnover problem was expected to be a useful tool to raise awareness for further examination of employee turnover problems. The thesis reveals that the model is substantially useful to explain job satisfaction among DGT employees (stayers), however, it is not fully effective in capturing employee turnover problems in Indonesia’s DGT. The model assumed organisational stability, while organisational change is more prevalent not only in the private sector, but also in the public sector. This research concludes that employees’ intentions/decisions in staying or leaving the DGT were rooted in organisational change and changes in its HR practices. The uncertainty tied into the reforms was found to be an important factor in influencing employees’ attitudes and behaviour toward their jobs.